Correlation of the Interferon Gamma Point +874 A/T Gene Polymorphism with the Occurrence of Schizophrenia - Agnes Felicia Lubis; Eddy Mart Salim; Zen Hafy (Jurnal Penelitian Pendidikan IPA, 2023)
Schizophrenia is a mental illness characterized by delusions and hallucinations. Several investigations have revealed that the immune system and genetic factors have a role in the development of schizophrenia. Interferon gamma is one of the genes thought to have a role in the development of schizophrenia, and many studies have reported the involvement of interferon-gamma (IFN-Î³) in neuropsychiatry. This study aims to determine the relationship between the Interferon-Î³ +874 A/T Gene Polymerphism with the incidence of Schizophrenia. A case control study was conducted at the hospital. Ernaldi Bahar Palembang for 3 months (February-April). There were 100 samples that met the inclusion criteria, of which 50 patients were cases and 50 respondents were healthy controls. Analysis of data using computerized data processing applications. The sampling method in this study is the matching sampling method. The results showed that the frequency of the A allele in the case group was 50 and in the control group was 69, while the frequency of the T allele in the case group was 50 and the control group was 31. The analysis of the results showed that the frequency of the T allele was higher in the schizophrenia group than the control group with value (p = 0.006), with an OR value of 2.226. There was a significant relationship between the case group and the control group. Individuals with the T allele have a 2,226 higher risk of developing schizophrenia than individuals with the A allele